Sitagliptin for the prevention of stress hyperglycemia in patients without diabetes undergoing coronary artery bypass graft (CABG) surgery. Issue 1 (3rd September 2019) - Cardona, Saumeth; Tsegka, Katerina; Pasquel, Francisco J; Fayfman, Maya; Peng, Limin; Jacobs, Sol; Vellanki, Priyathama; Halkos, Michael; Guyton, Robert A; Thourani, Vinod H; Galindo, Rodolfo J; Umpierrez, Guillermo
Abstract : Aims: To determine if treatment with sitagliptin, a dipeptidyl peptidase-4 inhibitor, can prevent stress hyperglycemia in patients without diabetes undergoing coronary artery bypass graft (CABG) surgery. Methods: We conducted a pilot, double-blinded, placebo-controlled randomized trial in adults (18–80 years) without history of diabetes. Participants received sitagliptin or placebo once daily, starting the day prior to surgery and continued for up to 10 days. Primary outcome was differences in the frequency of stress hyperglycemia (blood glucose (BG) >180 mg/dL) after surgery among groups. Results: We randomized 32 participants to receive sitagliptin and 28 to placebo (mean age 64±10 years and HbA1c: 5.6%±0.5%). Treatment with sitagliptin resulted in lower BG levels prior to surgery (101±mg/dL vs 107±13 mg/dL, p=0.01); however, there were no differences in the mean BG concentration, proportion of patients who developed stress hyperglycemia (21% vs 22%, p>0.99), length of hospital stay, rate of perioperative complications and need for insulin therapy in the intensive care unit or during the hospital stay. Conclusion: The use of sitagliptin during the perioperative period did not prevent the development of stress hyperglycemia or need for insulin therapy in patients without diabetes undergoing CABG surgery.